Predicting the attitude towards critical thinking skills of undergraduate students based on thinking styles - Anuar, Nor Azlin; Yusoff, N. S.; Sugumar, Thivyah Nair; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study is conducted to research whether or not a specific thinking style can predict critical thinking skills of undergraduate students in the Faculty of Educational Studies of Universiti Putra Malaysia. This study involves undergraduate students in year 1 until year 4 with their ages ranging from 19-24 years old. It is expected that there will be a significant difference between thinking styles and attitude toward critical thinking skills among undergraduate students. Through a series of ANOVAs, it is expected that executive, judicial and legislative thinking styles could each predict a certain level of critical thinking skills among undergraduate students.